Implementation Of The School Budget And Activity Plan (ARKAS) Application Policy In Realizing Good Governance In Junior High Schools - Ismatuzzaeni Ismatuzzaeni; Ilham Wahyudin; Siti Khumayah; Sri Wulandari (Al-Makki Publisher, 2024)
This study aims to analyze the Implementation of the School Activity Plan and Budget (ARKAS) Application policy in Realizing Good Governance in Junior High Schools, this research uses qualitative research with the type of case study research (Field Research). The data collection techniques used are observation, interviews, and documentation. Data analysis uses triangulation techniques, namely by displaying data, reducing data, and finally drawing conclusions. This research examines the ARKAS application technology used in realizing good governance in the field of BOS fund management. The implementation of the ARKAS policy reflects the concept of e-government by providing easier access to information on activity plans and budget allocations, enabling active participation in the decision-making process. The results of this study reveal that technology can be used optimally to achieve a goal. Through ARKAS, information related to activity plans and budget allocations can be accessed more easily by various stakeholders, which contributes to increased participation, and public trust and still refers to the applicable legal rules. The increased transparency and accountability achieved through ARKAS policy implementation has important implications, obstacles, and efforts in the context of financial management in educational institutions.